LATE-ONSET RADIATION-INDUCED VASCULOPATHY AND ISCHEMIC STROKE 20 YEARS AFTER IRRADIATION - Cho, Kyung-Hee; Han, Sungmin (17th World Stroke Congress (WSC 2025), 2025)
Background Radiotherapy is a useful modality for the treatment of brain tumors, but may induce brain degeneration, tumor formation, and vasculopathy in the irradiated field. We describe a case of a young stroke patient who presented an ischemic stroke because of occlusion of basilar artery, 20 years after radiotherapy against brain tumor. CASE A 35-year-old man suddenly developed right hemiparesis and slurred speech. His medical history was remarkable for brain tumor diagnosed at 15 years of age with operation, radiation, and chemotherapy. Magnetic resonance (MR) images showed a new cerebral infarction in the pons (Figure A) and previous craniotomy at occipital bone, severe atrophy of bilateral cerebellum. MR angiography revealed severe stenoocclusive lesions at both distal vertebral arteries and multifocal stenosis with underlying hypoplastic change of basilary trunk (Figure B). He was medically treated with active rehabilitation. Our presumptive diagnosis was pontine infarction secondary to late-onset radiation-induced vasculopathy. His stroke risk factor workup showed slightly elevated hemoglobin A1c (6.4%) and elevated low-density lipoprotein at 196 mg/dL, which were considered likely contributing factors. Conclusions Our patient’s presentation with stroke symptoms and imaging findings resembling the ischemic stroke commonly seen in older adults suggest that radiation combined with other risk factors (hyperlipidemia and diabetes) might accelerate the pathogenesis of large vessel disease. In young adult with history of brain tumor treated with radiation, identifying those at risk for delayed cerebrovascular complications is an important task. Measures to minimize radiation to the posterior fossa during treatment could potentially decrease long-term risk of radiationinduced vasculopathy and stroke in brain tumor survivors.